Angiotensin II-upregulated MAP kinase phosphatase-3 modulates FOXO1 and p21 in adrenocortical H295R cells - Mori Sequeiros, María de Las Mercedes (2020)
MAPK phosphatases (MKP) downregulate the activity of mitogen-activated protein kinases (MAPK), such asERK1/2, and modulate the processes regulated by these kinases. ERK1/2 participate in a wide range of processesincluding tissue-specific hormone-stimulated steroidogenesis. H295R cells are a suitable model for the study ofhuman adrenal cortex functions, particularly steroid synthesis, and respond to angiotensin II (Ang II) triggeringERK1/2 phosphorylation in a transient fashion. MKP-3 dephosphorylates ERK1/2 and, as recently reported,forkhead box protein 1 (FOXO1). Here, we analyzed MKP-3 expression in H295R cells and its putative regulationby Ang II. Results showed the expression of MKP-3 full length (L) and a short splice variant (S), and the upregulationof both isoforms by Ang II. L and S messenger and protein levels increased 30 min after Ang II stimulationand declined over the next 3 h, a temporal frame compatible with ERK1/2 dephosphorylation. In addition, FOXO1activation is known to include its dephosphorylation and nuclear translocation. Therefore, we analyzed the effectof Ang II on FOXO1 modulation. Ang II induced FOXO1 transient phosphorylation and translocation and also theinduction of p21, a FOXO1-dependent gene, whereas MKP-3 knock-down reduced both FOXO1 translocation andp21 induction. These data suggest that, through MKP-3, Ang II counteracts its own effects on ERK1/2 activity andalso triggers the activation of FOXO-1 and the induction of cell cycle inhibitor p21. Taken together, the currentfindings reveal the participation of MKP-3 not only in turn?off but also in turn-on signals which control importantcellular processes.